Answer:
Explanation:
- Let the demand equation be P = X + YQ
- at P = $24, Q = 11000units
- 24 = X + 11000Y.............equation 1
Substitute the value of X in equation 1
- hence demand equation ; P = X + YQ , P =61 - 0.00336Q
Similarly, let the supply equation be P = Z + wQ
- at P = $24, Q = 11000units
- 24 = Z + 11000w....................equation 2
- from equation P = Z + wQ, 3 = Z
Substitute the value of Z in equation 2
- 24 = Z + 11000w, but Z = 3
- hence the supply equation becomes, P = 3 + 0.00191w